2015
DOI: 10.1159/000371725
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone Replacement Therapy in Hypogonadal Men Following Prostate Cancer Treatment: A Questionnaire-Based Retrospective Study among Urologists in Bavaria, Germany

Abstract: a mean follow-up of 39.8 months, no biochemical relapse was observed. Conclusion: To date, there is no clear evidence to withhold TRT from hypogonadal men after curative PCa treatment. Our findings, although with limitations, fit in with the available data showing that TRT does not put patients at an increased risk after curative treatment of PCa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 35 publications
0
17
1
2
Order By: Relevance
“…A 2015 electronic survey of North American members of the Sexual Medicine Society of North America (SMSNA) revealed that a current or previous diagnosis of prostate cancer did not hinder physicians from prescribing TRT (41). These findings contrasted with a similarly designed 2015 German study which showed that German urologists were far less likely than their American counterparts to prescribe TRT to patients with a history of prostate cancer (42). …”
Section: Testosterone Prescribing Patternscontrasting
confidence: 68%
“…A 2015 electronic survey of North American members of the Sexual Medicine Society of North America (SMSNA) revealed that a current or previous diagnosis of prostate cancer did not hinder physicians from prescribing TRT (41). These findings contrasted with a similarly designed 2015 German study which showed that German urologists were far less likely than their American counterparts to prescribe TRT to patients with a history of prostate cancer (42). …”
Section: Testosterone Prescribing Patternscontrasting
confidence: 68%
“…In a recent German survey-based retrospective study, researchers sent questionnaires to all registered urologists in Bavaria, Germany [65]. Forty-six percent ( n = 193) responded to the request, which inquired about the urologist's experience with testosterone therapy in men with a history of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-six percent ( n = 193) responded to the request, which inquired about the urologist's experience with testosterone therapy in men with a history of prostate cancer. Among the 193 urologists, only 32 cases of testosterone therapy in men with prostate cancer were reported [65]. In a 2012 description of international testosterone utilization patterns, Gooren and Behre [11] provide updated follow-up data from a prior 2006 analysis to compare usage in 2010.…”
Section: Discussionmentioning
confidence: 99%
“…Of 72 relevant studies, 13 met criteria for inclusion (3,10,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). Primary human studies were included, and reviews, systematic reviews and meta-analyses were excluded.…”
Section: Study Selectionmentioning
confidence: 99%
“…For these studies, the authors' definition of high risk was accepted. Six of the included studies were not designed to group patients by risk level (3,28,30,(33)(34)(35), but included sufficient information to ascertain patients' risk level using the d'Amico criteria.…”
Section: Data Extractionmentioning
confidence: 99%